Michael Jackson Livin Bucharest:The Dangerous Tour - Morahan, Andrew; Siedah Garrett; Michael Jackson; Phinnessee, Darryl (Romania company contact information, 2005)
Live in Bucharest: The Dangerous Tour is a live concert DVD released by Michael Jackson in 2005. The DVD was previously included with the Michael Jackson: The Ultimate Collection box set. The concert took place during Jackson's first leg on his Dangerous World Tour on October 1, 1992 at the Bucharest National Stadium, with a sold-out attendance of 70,000. This concert is the only concert by Jackson that has been officially released on DVD in the United States. The only other official release by Michael Jackson was a VHS of his HIStory Tour concert in Seoul, South Korea, and it was released only in South Korea.
Language: English Subtitles: No subtitle
Keywords: Music -- Instruction and study